The right tool for the job - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Dibble sticks, donkeys and diesels: machines in crop product:ion is a study of agricultural mechanization from simple hand tools to tractors. It provides the non-agricultural engineer with the information needed to understand why particular designs...